Morphological variations observed in Trichoderma asperellum isolated from commercial products - Foyate, Meshu Shewarega (International Multidisciplinary Research Journal, 2023)
Genus Trichoderma contains many species that are of great economic importance because of their ability to suppress pathogens and enhance their biocontrol capabilities against soil borne pathogens. In order to utilize the full potential of Trichoderma species in specific applications, precise identification and characterization are vital. The use of molecular markers has given a boost to the analysis of the accurate variation among various isolates of bio-agents. The present study was carried out to estimate the morphological diversity among commercial products of Trichoderma. Trichoderma based commercial products produced by different firms and made available for sales were collected from Akola and Nagpur markets. A total of eight isolates were isolated from talc powder carrier based samples on TSM. The Trichoderma isolates were differentiated by colony characters and morphological features. All isolates showed different growth patterns, colony colour, colony type, pigmentation and morphological characters like phialides, conidial size and shape.